2018
DOI: 10.3390/ijerph15081764
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of School-Based Physical Activity Interventions on Cardiorespiratory Endurance in Primary School-Aged Children: A Meta-Regression

Abstract: The purpose of this study was to examine potential moderators of school-based physical activity interventions on cariorespiratory endurance in primary school-aged children using meta-regression. An Internet search with several databases was employed, extracting school-based pediatric physical activity intervention studies published within the past 30 years. Studies were included if there was a control or comparison group, if the study sample included primary school-aged children, if the targeted outcome of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…A 4-week intervention was chosen to best accommodate the school’s schedule. In previous studies, a 4-week intervention was a feasible timeline to see improvement in students’ PA levels through the classroom-based PA curriculum [7,12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 4-week intervention was chosen to best accommodate the school’s schedule. In previous studies, a 4-week intervention was a feasible timeline to see improvement in students’ PA levels through the classroom-based PA curriculum [7,12].…”
Section: Methodsmentioning
confidence: 99%
“…Increasing PA among children through school wide PA promotion has been gaining momentum in the U.S. To that end, schools are encouraged to implement Comprehensive School Physical Activity Programs (CSPAP) which encompasses quality physical education, before, after, and during school activities, as well as activities that engage school staff, family, and the community [6]. School-based PA interventions have been found to have health benefits, especially in improving cardiorespiratory endurance among children [7]. A strategy to increase PA during the school day is through classroom-based PA curriculum, where teachers lead short bouts of activities either during or between classroom instructions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous research has shown that interventions do not need to be complex or long in duration to be effective in improving children's aerobic fitness levels. Burns et al concluded from their meta-regression that both the intervention length and the number of intervention components did not modify the effect of the interventions on aerobic fitness [8].…”
Section: Introductionmentioning
confidence: 99%
“…Schools can function as an ideal venue for physical activity programs [7] since school attendance is mandatory and children spend a substantial amount of time at school. Burns et al conducted a meta-regression on a wide variety of school-based physical activity interventions and aerobic fitness, and found that school-based physical activity interventions have significant positive effects on aerobic fitness in primary-school-aged children [8]. Successful implementation is essential to the effectiveness of school-based physical activity interventions and is partially dependent on the willingness of the school personnel to allocate time in the curriculum for the intervention [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, whilst not advocating for the implementation of single-component interventions overall, the value of these interventions is not to be undermined. For example, research has indicated that school-based PA interventions have been shown to have a significant effect on cardiorespiratory endurance in primary school-aged children, and the intervention component number does not modify this significant effect [25].…”
Section: Introductionmentioning
confidence: 99%